Primary Care Clinicians Attitudes and Knowledge of Pharmacogenetics in a Large, Multi-state, Healthcare System - Olander, Megan (Innov Pharm, 2018)
BACKGROUND: Considerable progress has been made in the way of pharmacogenetic research and the development of clinical recommendations; however, its implementation into clinical practice has been slower than anticipated. We sought to better understand its lack of clinical uptake within primary care. AIM: The primary objective of this survey was to ascertain primary care clinicians’ perceptions of pharmacogenetic use and implementation in an integrated health system of metropolitan and rural settings across several states. METHODS: Primary care clinicians (including MDs, DOs, NPs, and PAs) were invited to participate in a survey via email. Questions about pharmacogenetics knowledge and perceptions were presented to assess current understanding and usage of pharmacogenetics in practice. RESULTS: The rate of response for the survey was 17%. Of the 90 respondents, 58% were female, 69% were MDs/DOs, 20% were NPs, and 11% were PAs. Fifty-eight percent of respondents received their clinical degree in or after 2000. Ninety percent of respondents noted that they were uncomfortable ordering a pharmacogenetics test, with 76% stating they were uncomfortable applying the results of a pharmacogenetic test. Notably, 78% of respondents were interested in having pharmacogenetic testing available through Medication Therapy Management (MTM) services, although PAs were significantly less interested as compared to NPs and MD/DOs. Ninety-five percent of respondents were interested in a clinical decision support tool relevant to pharmacogenetic results. CONCLUSIONS: As a whole, prescribing clinicians in primary care clinics are uncomfortable in the ordering, interpreting, and applying pharmacogenetic results to individual patients. However, favorable attitudes towards providing pharmacogenetic testing through existing MTM clinics provides the opportunity for pharmacists to advance existing practices.